Calcium and strontium stable isotopes reveal similar behaviors of essential Ca and nonessential Sr in stream food webs. Issue 2 (9th February 2022) - Nitzsche, Kai Nils; Wakaki, Shigeyuki; Yamashita, Katsuyuki; Shin, Ki‐Cheol; Kato, Yoshikazu; Kamauchi, Hiromitsu; Tayasu, Ichiro
Abstract: Recent studies showed the potential of stable isotopes of the macronutrient calcium (δ 44/40 Ca) and nonessential strontium (δ 88/86 Sr) as new trophic level indicators in terrestrial vertebrates and marine teleost fishes. In this study, we tested whether similar Ca and Sr isotopic fractionation trends existed in macroinvertebrate‐dominated stream food webs compared to vertebrates despite their physiological differences. We have determined the δ 44/40 Ca and δ 88/86 Sr values as well as the 87 Sr/ 86 Sr ratios of stream macroinvertebrates and small gobies and their potential metal sources (stream water, periphyton, and terrestrial plant litter) in upper and lower reaches of two streams in the Lake Biwa catchment, central Japan. The 87 Sr/ 86 Sr ratios revealed that stonefly nymphs, crustacea, and gobies mostly relied on aquatic Sr sources. Higher 87 Sr/ 86 Sr ratios of some crane fly and caddisfly larvae, mayfly, dobsonfly, and dragonfly nymphs indicated greater terrestrial contributions via plant litter. Positive correlations between the δ 44/40 Ca and δ 88/86 Sr values implied that similar Ca and Sr sources existed, and that Ca and Sr stable isotopes underwent similar fractionation trends although Sr was not essential. The δ 44/40 Ca and partly the δ 88/86 Sr values were positively correlated with Sr/Ca ratios and negatively with δ 15 N values indicating trophic effects on Ca and Sr stable isotopes. The enrichment of 44 Ca and 88 Sr in large filter‐feeding caddisfly larvae was a notable exception from these trophic trends. Our data confirm that the trophic 44 Ca and 88 Sr depletion observed for marine teleost fishes and terrestrial vertebrates also applied to macroinvertebrate‐dominated stream food webs despite their different physiologies indicating that shared mechanisms of Ca and Sr isotopic fractionation may exist at the cellular or molecular level between these taxa.